CULTURAL ADAPTATION OF A LIFESTYLE EXERCISE INTERVENTION FOR OLDER AFRICAN AMERICANS: RESEARCH RESULTS. (11th November 2018) - Gretebeck, K; Green-Harris, G; Ward, E; Houston, S; Skora, T; Brown, M; Means, J; Gretebeck, R
Abstract: Older African Americans (AAs) have high disability rates and low participation in physical activity (PA) programs as programs are not culture-specific. The purpose of this study was to culturally adapt Physical Activity for Life for Seniors (PALS) for older AAs and evaluate physical function, PA and self-regulation (SR) and feasibility of implementation in AA communities. PALS is an 8 ½ month evidence-based lifestyle behavior-change intervention designed to improve physical function (usual gait speed-UGS, timed up and go-TUG, 6-minute walk-6MW) and increase PA (CHAMPS questionnaire) through SR (Petosa's PA SR questionnaire). This pre-posttest design utilized community participatory research methodology. Cultural adaptation was an iterative process including community advisory boards, PALS trainers and participants and researchers. Following cultural adaptation, 4 PALS programs were implemented in government subsidized housing complexes and one community center in 2 urban cities. Measures were assessed at baseline, after the 10-week group exercise class, and 6 months after the 10-week program. The sample comprised 40 AA (6 males and 34 females, 59–85 years old (M=67.9, sd=6.40), mean BMI 34.23 (sd=9.19, range 14.99–57.47). 47.5% were morbidly obese. Results indicated improvements (p<.01) in TUG, UGS, 6MW, moderate intensity and total PA and SR immediately following the 10-week group class and were maintained for 6 months (p<.01). The culturally adapted PALS was effective in improving physical function, PA and SR in AAs. PALS is feasible to implement in AA communities with no difficulty recruiting participants, low attrition (n=4) and no injuries. This low-cost program was well-received by participants and community agencies.